The Efficiency, Predictability and Safety Between Custom-Q Femotsecond Laser In Situ Keratomileusis and Second (Visumax 800) Generation Keratorefractive Lenticule Extraction Surgery - Chia-Yi Lee; Shun-Fa Yang; Ie-Bin Lian; Hung-Chi Chen; Jing-Yang Huang; Chao-Kai Chang (Diagnostics, 2025)
Background/Objectives: To evaluate the postoperative outcomes between the second-generation keratorefractive lenticule extraction (KLEx) surgery and femtosecond laser in situ keratomileusis (FS-LASIK). Methods: A retrospective cohort study was conducted and subjects received second-generation KLEx and FS-LASIK surgeries were enrolled. A total of 124 and 102 eyes were selected into the second-generation KLEx and FS-LASIK groups after exclusion. The primary outcomes were the postoperative uncorrected distance visual acuity (UDVA), spherical equivalent (SE), amount of astigmatism, and best-correct visual acuity (BCVA). The independent t-test was applied to compare the primary outcomes between groups. Results: The mean UDVA three months postoperatively showed insignificant differences between the two groups (p = 0.999). At the final visit, there were 113 (91.12%) and 96 (94.12%) subjects who reached UDVA 20/20 in the FS-LASIK and second-generation KLEx groups and the difference was statistically insignificant (p = 0.455), and the second-generation KLEx group illustrated a higher UDVA improvement (p = 0.046). The SE three months postoperatively showed insignificant difference between groups, whether the absolute value or the ratio of SE within ±0.50 D or ±1.00 D (all p > 0.05). The vector analysis indicated that the difference vector (DV) was significantly lower in the second-generation KLEx group (p = 0.033). The ratio of loss of more than 1 line BCVA showed insignificant differences between the two groups (all p > 0.05). In addition, the risk of postoperative dry eye disease (DED) was significantly higher in the FS-LASIK group (p = 0.031). Conclusions: The efficiency and predictability between second-generation KLEx and FS-LASIK surgeries are similar, while more DED occurred after FS-LASIK surgery.